Principal Leadership Strategies in Enhancing The Digital Literacy Competence of Teachers and Education Personnel in Rokan Hulu - Fadri Rahman; Nurtanio Agus Purwanto (Indonesian Technology and Education Journal, 2026)
Digital transformation in education requires school principals to move beyond administrative leadership and actively shape the digital capacity and work practices of teachers and education personnel. However, empirical evidence remains limited regarding how such leadership strategies are implemented in resource-constrained regional schools and whether similar strategic patterns emerge across schools with different organizational scales. This study examined principal leadership strategies for strengthening digital literacy among teachers and education personnel in two reference digital public junior secondary schools in Rokan Hulu Regency, Indonesia. A descriptive qualitative multiple-case study design was employed involving eight purposively selected informants comprising two principals, four teachers, and two education personnel. Data were collected through semi-structured interviews, non-participant observations, and document analysis and were analyzed using within-case and cross-case procedures based on the interactive model of data condensation, data display, and conclusion drawing, with source and method triangulation used to strengthen credibility. The findings identified four interrelated leadership strategies: mapping digital needs and competencies, applying gradual and adaptive capacity-building approaches, optimizing internal and district-level resources, and developing a sustainable digital work culture. These strategies were implemented through internal training, peer mentoring, supervision-based monitoring, and integration of digital-literacy initiatives into routine school management. Across both cases, principal leadership was the most consistently emphasized supporting factor, whereas disparities in digital skills and limited professional-development time represented the most prominent barriers. The findings extend transformational and distributed leadership perspectives by showing how adaptive and shared leadership practices can support school digitalization across institutions with different resource scales. Nevertheless, because digital competence was not directly measured, the findings should be interpreted as evidence of perceived and observed implementation rather than verified competence improvement.